2007
DOI: 10.1378/chest.06-1549
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Oscillatory Ventilation for Adult Patients With ARDS

Abstract: High-frequency oscillatory ventilation (HFOV) is characterized by the rapid delivery of small tidal volumes (Vts) of gas and the application of high mean airway pressures (mPaws). These characteristics make HFOV conceptually attractive as an ideal lung-protective ventilatory mode for the management of ARDS, as the high mPaws prevent cyclical derecruitment of the lung and the small Vts limit alveolar overdistension. In this review, we will summarize the literature describing the use of HFOV in adult patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
66
0
8

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 73 publications
0
66
0
8
Order By: Relevance
“…H igh-frequency oscillation (HFO) is suggested for adults with severe acute respiratory distress syndrome (ARDS) [1,2]. During HFO, tidal volumes of ,3.5 mL?kg -1 predicted body weight are administered at o3 Hz and mean airway pressure (P aw) ranges 22-40 cmH 2 O [1][2][3].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…H igh-frequency oscillation (HFO) is suggested for adults with severe acute respiratory distress syndrome (ARDS) [1,2]. During HFO, tidal volumes of ,3.5 mL?kg -1 predicted body weight are administered at o3 Hz and mean airway pressure (P aw) ranges 22-40 cmH 2 O [1][2][3].…”
mentioning
confidence: 99%
“…During HFO, tidal volumes of ,3.5 mL?kg -1 predicted body weight are administered at o3 Hz and mean airway pressure (P aw) ranges 22-40 cmH 2 O [1][2][3]. Animal lung injury data favour HFO over lung-protective conventional mechanical ventilation (CMV) [4].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies of HFOV use for adult ARDS patients with severe hypoxemia and high plateau airway pressures have verified significant improvement in oxygenation and suggest that early initiation may have better outcomes. 3,4,19 It has also been shown that HFOV is effective and safe in correcting oxygenation failure associated with ARDS in surgical patients. 20 In this severe TRALI case, severe hypoxemia persisted despite pressure control ventilation support with 100% oxygen and PEEP of 18 cm H 2 O for 12 hours.…”
Section: Discussionmentioning
confidence: 99%